Technological Management of the Barriers to Learning and Participation in Basic Education Students by Using a Methodological Approach - Anzures-Garcia, Mario; Sánchez Gálvez, Luz A.; Larios Gómez, Mariano; Díaz Hernández, Osmar; Cortes Jiménez, Gabino (International Journal of Combinatorial Optimization Problems and Informatics, 2024)
This work proposes a methodological approach to manage technologically the barriers to learning and participation that prevent students from accessing knowledge effectively. The aim is to allow their inclusion both in the educational environment and society. This approach is based on various methodological resources —Constructivism, the Social Model of Disability, the Ecological Model, and Differentiated Pedagogy— provided by the regular education support services unit. This assistance helps students with special educational needs, such as those with a disability, outstanding abilities, and aptitudes, or difficulties in developing competencies in the training fields of the curriculum. Additionally, it helps students with other conditions, such as Autism Spectrum Disorder, Attention Deficit and Hyperactivity Disorder, language problems, learning, and behavioral problems. Furthermore, user-centered design methodologies like Design Thinking, and agile development such as SCRUM, are integrated into this approach. Finally, the ADARA technological platform is created to test the feasibility of the proposed approach.